Surgical and oncologic outcomes following arterial resection and reconstruction for advanced solid tumors. Issue 8 (8th September 2021) - Cruz, Sylvia M.; Basmaci, Ugur N.; Bateni, Cyrus P.; Darrow, Morgan A.; Judge, Sean J.; Monjazeb, Arta M.; Thorpe, Steven W.; Humphries, Misty D.; Canter, Robert J.
Abstract: Background and Objectives: Although arterial involvement for advanced tumors is rare, vascular resection may be indicated to achieve complete tumor resection. Given the potential morbidity of this approach, we sought to evaluate perioperative outcomes, vascular graft patency, and survival among patients undergoing tumor excision with en bloc arterial resection and reconstruction. Methods: From 2010 to 2020, we identified nine patients with tumors encasing or extensively abutting major arterial structures for whom en bloc arterial resection and reconstruction was performed. Results: Mean age was 53 ± 20 years, and 89% were females. Diagnoses were primary sarcomas (5), recurrent gynecologic carcinomas (3), and benign retroperitoneal fibrosis (1). Tumors involved the infrarenal aorta (2), iliac arteries (6), and superficial femoral artery (1). Three patients (33%) had severe perioperative morbidity (Grade III + ) with no mortality. At a median follow‐up of 23 months, eight patients (89%) had primary graft patency, and five patients (56%) had no evidence of disease. Conclusions: Arterial resection and reconstruction as part of the multimodality treatment of regionally advanced tumors is associated with acceptable short‐ and long‐term outcomes, including excellent graft patency. In appropriately selected patients, involvement of major arterial structures should not be viewed as a contraindication to attempted curative surgery.